2021
DOI: 10.7759/cureus.15427
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term Medical Mission in Rural Nepal: Chief Complaints, Medications Dispensed, and Unmet Health Needs

Abstract: BackgroundAlthough Nepal is striving to expand primary health services for its citizens, many remote areas have limited access to basic health care. Short-term medical missions (STMMs) are one way of supplementing human resources for health in underserved areas. This article describes the chief complaints, medications dispensed, and unmet health needs during an STMM in rural Nepal. MethodsThis study is a retrospective analysis of data collected during an STMM that occurred in October 2017. Deidentified data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A two-day health camp in Thonche village, Nepal was conducted where out of 443 patients seen, 28.2% were musculoskeletal cases 12 . In health camps conducted in Nuwakot by Pambos et al ., musculoskeletal problems were the second most common diagnosis which was present in 19.3% of adults ( n =1574) presenting to the camp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A two-day health camp in Thonche village, Nepal was conducted where out of 443 patients seen, 28.2% were musculoskeletal cases 12 . In health camps conducted in Nuwakot by Pambos et al ., musculoskeletal problems were the second most common diagnosis which was present in 19.3% of adults ( n =1574) presenting to the camp.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results are seen in this study as well where farmers constitute the bulk of the population presenting to the health camp (68.28%). Both of these studies showed that musculoskeletal problems are also one of the causes of considerable unmet disease burden, especially in the remote areas of Nepal [12,13] . There are studies describing specialist health camps for diabetes, cataract, gynecology, and otorhinolaryngology but there have been no studies about specialized orthopedic health camps [13] .…”
Section: Discussionmentioning
confidence: 99%
“…In the Nepalese context, there is a lack of robust healthcare infrastructures, particularly in remote and rural areas, where basic medical facilities, such as hospitals and clinics are scarce or nonexistent (Bitter et al, 2021). This deficit intertwines with profound accessibility issues, exacerbating healthcare disparities because difficult terrains and inadequate transportation hinder the delivery of crucial medical services to these remote regions (Cothran, 2016).…”
Section: Challenges Facing Healthcare Access and Empowerment Of Healt...mentioning
confidence: 99%